Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369